The necessary professional competencies for teaching mathematics at the College of Basic Education at Al-Mustansiriya University (Journal of the College of Basic Education, 2022)
One of the most important motives that aroused the researcher's interest is the low level of students' achievement in mathematics, and a large percentage of teachers believe that the methods used by teachers in teaching are difficult for students during teaching (Al-Awadi, 1981, pp. 23-25).Therefore, the preparation of the teacher is an essential pillar in the educational process, and if the teacher is one of the most important axes of the educational process, then his preparation and training are among the advanced matters that receive priority in terms of concern in many countries of the world, and because an effective teacher needs a number of professional competencies.The teaching is the point of recurrence, and it is the basis, and when the teaching is reformed, the student is reformed, and by reforming the student and directing him properly, the matter leads to the reformation of the entire nation. (Damaa, 1974, p. 21).Therefore, the problem of the research is to identify a list of the professional competencies necessary for teachers of the Mathematics Department in the College of Basic Education.